Breeding phenological response to spring weather conditions in common Finnish birds: resident species respond stronger than migratory species. (18th January 2017) - Kluen, Edward; Nousiainen, Riikka; Lehikoinen, Aleksi
Abstract : National bird‐nest record schemes provide a valuable data source to study large‐scale changes in basic breeding biology and effects of climate change on birds. Using nest‐record scheme data from 26 common Finnish breeding bird species from whole Finland, we estimated the laydate of the first egg for 129 063 nesting attempts. We then investigated the relationship of mean spring temperature and spring precipitation sum to changes in the onset of laying over the period 1961–2012. In addition, we examine differences in response to these climatic variables for species grouped for different life history strategies; migration, diet and habitat. Finally, we test whether body size is related to the strength of phenological response. We show that 26 common Finnish breeding bird species have advanced their laying dates over time and to an increase in the mean spring temperature over the study period. When species are grouped according life history strategies, we find that breeding phenological change is negatively associated with changes in the mean spring temperature where residents respond strongest to changes in mean spring temperature, but also short‐ and long‐distance migrants advance laydates with increasing spring temperatures. Breeding phenological change is also associated with spring precipitation, where resident species delay and short‐distance migrants advance the onset of breeding. In addition we find that omnivorous species respond stronger than insectivorous species to changes in spring temperature. In contrast to results from an earlier study, we do not find evidence that small‐sized species respond stronger to spring temperature than large‐sized species. As climate warming is predicted to continue in the future, long‐term citizen science schemes, such as the Finnish nest‐card scheme, prove to be a valuable cost‐effective way to monitor the environment and allow investigation into how species are responding to changes in their environment.